2021
DOI: 10.1172/jci.insight.144392
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling reveals biomarkers and pathways in type 2 diabetes risk

Abstract: Recent advances in proteomic technologies have made high-throughput profiling of low-abundance proteins in large epidemiological cohorts increasingly feasible. We investigated whether aptamer-based proteomic profiling could identify biomarkers associated with future development of type 2 diabetes (T2DM) beyond known risk factors. We identified dozens of markers with highly significant associations with future T2DM across 2 large longitudinal cohorts ( n = 2839) followed for up to 16 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 71 publications
(103 reference statements)
1
23
0
Order By: Relevance
“…Second, N-acetylserine may be a surrogate for other ACY1 substrates, including other N-acetylated amino acids, that are harmful in excess. A recent study showed that reducing the ratio of circulating N-acetylated amino acids to free amino acids by exogenous administration of ACY1 protein acutely improves glucose tolerance in mice ( 34 ). Third, given the diverse role of protein acetylation in cellular processes, including modulation of gene expression, protein stability, and signal transduction, impaired salvage of acetyl groups could be harmful to the proximal tubule ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, N-acetylserine may be a surrogate for other ACY1 substrates, including other N-acetylated amino acids, that are harmful in excess. A recent study showed that reducing the ratio of circulating N-acetylated amino acids to free amino acids by exogenous administration of ACY1 protein acutely improves glucose tolerance in mice ( 34 ). Third, given the diverse role of protein acetylation in cellular processes, including modulation of gene expression, protein stability, and signal transduction, impaired salvage of acetyl groups could be harmful to the proximal tubule ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Variants in c-MET also associate with circulating triglycerides at genome wide significance in humans consistent with a potential role for HGFAC in regulating triglyceride levels through activation of HGF (27). Moreover, increased levels of circulating HGF in people associate with features of cardiometabolic disease including obesity, risk for type 2 diabetes, and risk for cardiovascular disease (28)(29)(30)(31). Circulating HGF levels are influenced by variants in the HGFAC locus (32).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has described a strong positive correlation between ACY1 protein levels and type 2 diabetes (T2DM). 45 Through in vitro and in vivo experiments, the authors showed that increasing amounts of ACY1 decreased the ratio of N-acetyl/free amino acids, with a consequent effect on glucose and insulin homeostasis, possibly leading to b-cell exhaustion, reduced b-cell mass, and ultimately insulin deficiency and T2DM. In another recent study in a subset of participants from the INTERVAL study, a polygenic risk score for T2DM was associated with ACY1 protein levels, thus strengthening the link between ACY1 and T2D risk.…”
Section: Discussionmentioning
confidence: 99%